O Diferencial do origami em sala de aula: uma possibilidade de ensino para o ensino fundamental - Okuma, Rafael [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The purpose of this work is to present the activities that involve Origami and Mathematics Education, so that an exploratory study about the subject can be done, because this way it is familiar with the two themes (Origami and Mathematics Education). In addition, the works were published with the help of Mathematics, however, in addition to using the activities as BNCC activities to justify the use of Origami for Elementary School. To the development of activities, they were studied the Axioms of the development which are important to realize to any doubles. The end of the information cross between BNCC and Origami activities has a satisfactory result, since the different abilities with the folding were approached

O objetivo deste trabalho é apresentar atividades lúdicas que envolvessem o Origami e Educação Matemática, para isto foi feito um estudo exploratório a respeito, pois assim familiarizaria com os dois temas (Origami e Educação Matemática). Além de explorar os temas, foram analisados trabalhos que contêm atividades com a dobradura e Matemática, porém, além de identificar as atividades foram utilizadas as habilidades da BNCC (Base Nacional Comum Curricular) para justificar o uso do Origami para o Ensino Fundamental. Para o desenvolvimento das atividades, foram estudados os Axiomas da dobradura que são fundamentais para realização de qualquer dobra. Ao final do cruzamento de informações entre as habilidades da BNCC e as atividades com Origami, obteve-se um resultado satisfatório, já que foram abordadas diversas das habilidades com a dobradura
The Origami differential in the classroom: a teaching possibility for elementary school
Keywords: Origami; Geometria; Ensino fundamental; Trabalhos em papel; Geometry